Fifties Ethnicities : The Ethnic Novel and Mass Culture at Midcentury - Floreani, Tracy (Book collections on Project MUSE., 2013)
This book demonstrates how written and visual representations worked to construct definitions of ethnicity in mid-twentieth-century America.